2014
DOI: 10.1002/lary.24526
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between epistaxis, migraines, and triggers in hereditary hemorrhagic telangiectasia

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 65 publications
1
34
0
2
Order By: Relevance
“…By 6 months, compensatory polycythaemia [3] and higher cardiac outputs [9] have also reversed, and this is a useful time-point to assess sustained clinical responses to embolisation. A standard “Have you noticed any difference?” question is asked, intended to capture respiratory [2, 3] and neurological [4, 6, 10] symptoms. Surprisingly, both spontaneously and in response to this question, patients frequently reported that their nosebleeds had improved following this apparently unconnected treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By 6 months, compensatory polycythaemia [3] and higher cardiac outputs [9] have also reversed, and this is a useful time-point to assess sustained clinical responses to embolisation. A standard “Have you noticed any difference?” question is asked, intended to capture respiratory [2, 3] and neurological [4, 6, 10] symptoms. Surprisingly, both spontaneously and in response to this question, patients frequently reported that their nosebleeds had improved following this apparently unconnected treatment.…”
mentioning
confidence: 99%
“…The NRES Committee East Midlands-Derby 1 Research Ethics Committee approved the study and online launch at https://www1.imperial.ac.uk/nhli/cardio/vascular/pulmonary_vascular/hht_pavms/hhtsurvey/ The basic study design has been reported previously [10]. Briefly, online informed consent was obtained from all participants who were then asked to provide details on general aspects of their HHT phenotype, before proceeding to a series of questions regarding nosebleed responses to assessments and interventions.…”
mentioning
confidence: 99%
“…У пациентов с носовыми кровотечениями часто развивается железодефицит ная анемия [22]. Обследование пациентов с НГТ по казало, что 70% из них нуждаются в восполнении дефицита железа, а 20% из них проводили, по край ней мере, 10 переливаний крови [23].…”
Section: клиника и диагностикаunclassified
“…HHT nosebleeds are highly variable, and generally difficult to predict. However, in recent studies by our group, HHT patients reported that nosebleeds could be precipitated by certain food groups (13,14). Spontaneously volunteered precipitant foods included red wine, spices, chocolate, coffee, berries, oily fish, and other food items that contain high levels of naturally occurring salicylates and other anti-platelet agents (13).…”
Section: Introductionmentioning
confidence: 95%